Autophagy and LAP in the Fight against Fungal Infections: Regulation and Therapeutics - Vasileios Oikonomou; Giorgia Renga; Antonella De Luca; Monica Borghi; Marilena Pariano; Matteo Puccetti; Giuseppe Paolicelli; Claudia Stincardini; Claudio Costantini; Andrea Bartoli; Teresa Zelante; Luigina Romani (Hindawi Limited, 2018)
Phagocytes fight fungi using canonical and noncanonical, also called LC3-associated phagocytosis (LAP), autophagy pathways. However, the outcomes of autophagy/LAP in shaping host immune responses appear to greatly vary depending on fungal species and cell types. By allowing efficient pathogen clearance and/or degradation of inflammatory mediators, autophagy proteins play a broad role in cellular and immune homeostasis during fungal infections. Indeed, defects in autophagic machinery have been linked with aberrant host defense and inflammatory states. Thus, understanding the molecular mechanisms underlying the relationship between the different forms of autophagy may offer a way to identify drugable molecular signatures discriminating between selective recognition of cargo and host protection. In this regard, IFN-γ and anakinra are teaching examples of successful antifungal agents that target the autophagy machinery. This article provides an overview of the role of autophagy/LAP in response to fungi and in their infections, regulation, and therapeutic exploitation.